(3QSGdI aj GdYed HGdQHY GdeLjHs - (3YHO Gddg Hf Ndjd Hf jhSa, LeGd GdOjf GdeGQOGfj,J (B809 (3g` s
(3ChdgG (B:s
(3HYO GdOjHGLI (B: (3agPg QSGdI ai GdYed HGdQHY eTJedI Ydi ebOeI hYTQjf HGHkG hNGJeI aGdebOeI ai JSejI QSheg s
(3BNQgG (B:s
(3eG Hjf bOejc hGdYdGeI ajeG cGf agh Whd Pdc GdbGFe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B49 - (3U(B53s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B85 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B53s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B169 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B47 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3ejbGJ (B105) s
Keywords: (3Gdadcs